Mathematics in cyber research - Goethals, Paul L.; Scala, Natalie M. (Natalie Michele); Bennett, Daniel T. ([Place of publication not identified] : Chapman and Hall/CRC, 2022)
In the last decade, both scholars and practitioners have sought novel ways to address the problem of cybersecurity. Innovative outcomes have included applications such as blockchain as well as creative methods for cyber forensics, software development, and intrusion prevention. Accompanying these technological advancements, discussion on cyber matters at national and international levels has focused primarily on the topics of law, policy, and strategy. The objective of these efforts is typically to promote security by establishing agreements among stakeholders on regulatory activities. Varying levels of investment in cyberspace, however, comes with varying levels of risk; in some ways, this can translate directly to the degree of emphasis for pushing substantial change. At the very foundation or root of cyberspace systems and processes are tenets and rules governed by principles in mathematics. Topics such as encrypting or decrypting file transmissions, modeling networks, performing data analysis, quantifying uncertainty, measuring risk, and weighing decisions or adversarial courses of action represent a very small subset of activities highlighted by mathematics. To facilitate education and a greater awareness of the role of mathematics in cyber systems and processes, a description of research in this area is needed. Mathematics in Cyber Research aims to familiarize educators and young researchers with the breadth of mathematics in cyber-related research. Each chapter introduces a mathematical sub-field, describes relevant work in this field associated with the cyber domain, provides methods and tools, as well as details cyber research examples or case studies. Features One of the only books to bring together such a diverse and comprehensive range of topics within mathematics and apply them to cyber research. Suitable for college undergraduate students or educators that are either interested in learning about cyber-related mathematics or intend to perform research within the cyber domain. The book may also appeal to practitioners within the commercial or government industry sectors. Most national and international venues for collaboration and discussion on cyber matters have focused primarily on the topics of law, policy, strategy, and technology. This book is among the first to address the underpinning mathematics.
1. Combinatorics Cheyne Homberger 2. CryptographyGretchen L. Matthews, Aidan W. Murphy3. Algebraic Geometry Lubjana Beshaj4. TopologySteve Huntsman, Jimmy Palladino, Michael Robinson5. Differential Equations Parisa Fatheddin6. Network Science Elie Alhajjar7. Operations Research Paul L. Goethals, Natalie M. Scala, Nathaniel D. Bastian8. Data AnalysisRaymond R. Hill, Darryl K. Ahner9. StatisticsNita Yodo, Melvin Rafi10. Probability Theory David M. Ruth11. Game TheoryAndrew Fielder12. Number TheoryDane Skabelund13. Quantum TheoryTravis B. Russell14. Group TheoryWilliam Cocke, Meng-Che 'Turbo' Ho15. Ring TheoryLindsey-Kay Lauderdale
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Operations Research; COMPUTERS / Machine Theory; COMPUTERS / Cryptography; Computer science -- Mathematics; Cyberspace -- Mathematics; Operations research -- Mathematics